At the intersection of technology and law: distributed ledger technology and its impact on private law - Aslan, Simge (2025)
2009 gave us Bitcoin, a new virtual currency that was the first example and the starting point of a novel and disruptive technology, distributed ledger technology (DLT). Since then, the law of commerce has been getting more intertwined with the technology each day. A prominent aspect is the creation of a new type of asset, DLT assets. These assets are being bought and sold, and new business models are being created around them. From a legal perspective, their novelty lies in the fact that they are purely intangible assets that can be subject to an exclusive control by an individual. This thesis aims to explore the implications of DLT assets in private law, particularly property, secured transactions and insolvency law. It will address each subject of law in separate chapters and identify issues that might arise due to the novelty of the assets. The goal is to identify the common themes that arise regarding the effective accommodation of DLT assets within the relevant legal frameworks. The thesis will inquire whether DLT assets undermine or challenge any of the established principles of the chosen subjects of law, and assess the most recent developments and explore possible solutions via a theoretical and a comparative analysis.